A retrospective study on children with pulmonary arterial hypertension: A single-center experience - Kula, Serdar (Anatol J Cardiol, 2018)
OBJECTIVE: The aim of this study was to evaluate children with pulmonary arterial hypertension (PAH) regarding epidemiological characteristics, clinical status with respect to the WHO functional class (WHO-FC), prognostic factors, and efficacy of medical treatment. METHODS: A retrospective evaluation of 41 patients with PAH was made in the Pediatric Cardiology Unit, Gazi University Medical Faculty, between February 2006 and October 2015. RESULTS: Of the 41 patients included in this study, 51.2% were female. The median age was 60 months at first evaluation. The median follow-up was 60 months. At the start of the treatment, 43.9% patients were receiving combined drug therapy, and this rate increased to 60.9% by the last evaluation. The median time of adding a new medication to the therapy was 20 months. The 1- and 5-year survival rates were 94% and 86%, respectively. At the time of diagnosis, only pro-brain natriuretic peptide (proBNP) levels were associated with mortality (p=0.004), but at the last evaluation, 6-min walking test, proBNP and uric acid levels, and WHO-FC were also associated with survival (p=0.02, p=0.001, p=0.002, and p=0.05, respectively). CONCLUSION: With current treatment choices in experienced centers, positive results are obtained with respect to the functional status and survival rates of patients with PAH. At the time of diagnosis, only proBNP had a prognostic value, whereas at the last evaluation, WHO-FC, 6-min walking test, proBNP, and uric acid were reported prognostic factors. For preventing rapid progression, determination of factors that have an effect on prognosis, in particular, is extremely important.